Novel Techniques For Model-Code Synchronization - Angyal, László; Lengyel, László; Charaf, Hassan (Electronic Communications of the EASST, 2008)
The orientation of the current software development practice requires efficient model-based iterative solutions. The high costs of maintenance and evolution during the life cycle of the software can be reduced by using tool-aided iterative development. This paper presents how model-based iterative software development can be supported through efficient model-code change propagation. The presented approach facilitates bi-directional synchronization between the modified source code and the refined initial models. The backgrounds of the synchronization technique are three-way abstract syntax tree (AST) differencing and merging. The AST-based solution enables syntactically correct merge operations. OMG's Model-Driven Architecture describes a proposal for platform-specific model creation and source code generation. We extend this vision with the synchronization feature to assist the iterative development. Furthermore, a case study is also provided.